Ganoderma lucidum Polysaccharides Induce Macrophage-Like Differentiation in Human Leukemia THP-1 Cells via Caspase and p53 Activation - Hsu, Jia-Wei (Hindawi Publishing Corporation, 2011)
Differentiation therapy by induction of tumor cells is an important method in the treatment of hematological cancers such as leukemia. Tumor cell differentiation ends cancer cells' immortality, thus stopping cell growth and proliferation. In our previous study, we found that fucose-containing polysaccharide fraction F3 extracted from Ganoderma lucidum can bring about cytokine secretion and cell death in human leukemia THP-1 cells. This prompted us to further investigate on how F3 induces the differentiation in human leukemia cells. We integrated time-course microarray analysis and network modeling to study the F3-induced effects on THP-1 cells. In addition, we determined the differentiation effect using Liu's staining, nitroblue tetrazolium (NBT) reduction assay, flow cytometer, western blotting and Q-PCR. We also examined the modulation and regulation by F3 during the differentiation process. Dynamic gene expression profiles showed that cell differentiation was induced in F3-treated THP-1 cells. Furthermore, F3-treated THP-1 cells exhibited enhanced macrophage differentiation, as demonstrated by changes in cell adherence, cell cycle arrest, NBT reduction and expression of differentiation markers including CD11b, CD14, CD68, matrix metalloproteinase-9 and myeloperoxidase. In addition, caspase cleavage and p53 activation were found to be significantly enhanced in F3-treated THP-1 cells. We unraveled the role of caspases and p53 in F3-induced THP-1 cells differentiation into macrophages. Our results provide a molecular explanation for the differentiation effect of F3 on human leukemia THP-1 cells and offer a prospect for a potential leukemia differentiation therapy.